“There are So Many of Us” a history of the Izinkumbi and grouping processes in precolonial and colonial natal, c.1824 - 1862 - Ferreira, Angela (Department of Historical Studies, 2025)
This thesis examines the history of the people who came to be known as ‘Izinkumbi' — or ‘locusts' — in the period between 1820 and 1864 residing in the Mkhomazi-Mzimkhulu region of what is today the KwaZulu-Natal province of South Africa. It explores their origin in the 1820s when, with the support of the Zulu king, Shaka, numbers of Africans collected under the newly arrived English traders at Port Natal. By the 1830s, these trader adherents mobilised as the ‘Izinkumbi' in a war against Shaka's successor, Dingane. Since their inception, the Izinkumbi have occupied an ambiguous social space. Their mixed constitution and blending of African and European material culture and practices confused colonial attempts to categorise and place the Izinkumbi within the developing tribalscape. The research concludes that Izinkumbi — a name for a group of people that uses the isiZulu noun or ‘thing'class, ‘izi,' as opposed to the people class ‘ama,' — was a category reflecting a social process. The Izinkumbi were a shifting combination of different groups' shared pasts, living strategies, intentions and actions, forged in relation first to the rule of the Zulu kings and later to the British colonial government. The case of Izinkumbi brings much-needed attention to the history of southern KwaZulu-Natal. It also contributes to the literature on identity as a process in which agents participate rather than a given thing people have.